Depression in amyotrophic lateral sclerosis - Atassi, Nazem; Cook, Amanda; Pineda, Cristiana M. E.; Yerramilli-Rao, Padmaja; Pulley, Darlene; Cudkowicz, Merit (My University, 2011)
Depression is an under-recognized comorbidity associated with amyotrophic lateral sclerosis (ALS). The goals of this study were to prospectively estimate the prevalence of depression and other ALS related symptoms and to study the impact of depression on enrollment in research studies. One hundred and twenty-seven people with ALS completed the ALS Depression Inventory (ADI-12) and answered questions about ALS related symptoms and research study enrollment preferences. Demographics, ALS symptoms, medications, functional status, and research enrollment were compared between depressed and non-depressed patients. Results showed that the prevalence of mild and severe depression was 29% and 6%, respectively. More than one-third of our ALS patients were receiving anti-depressants to treat depression, sialorrhea, and pseudobulbar affect. Depression prevalence was not correlated with disease duration or progression. Except for anxiety, none of the ALS related symptoms predicted depression. The presence of depression did not have an effect on the decision to enroll in research studies. In conclusion, major depression is less common in our ALS cohort than in the general population. The diagnosis of depression can be masked by some ALS related symptoms and it has no impact on enrollment in ALS clinical trials.